2016
DOI: 10.1093/jac/dkw398
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ESBLs, AmpC β-lactamases and carbapenemases among Enterobacteriaceae isolates causing intra-abdominal and urinary tract infections in the Asia-Pacific region during 2008–14: results from the Study for Monitoring Antimicrobial Resistance Trends (SMART)

Abstract: The high resistance burden in Vietnam and the Philippines warrants aggressive control policies to combat the worsening trend in antimicrobial resistance among Enterobacteriaceae species causing IAIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 19 publications
4
53
3
1
Order By: Relevance
“…Our study revealed a prevalence of the AmpC producing gene of 14.75% among ESBL producing Enterobacteriaceae. In our study, we found out that among all the AmpC producers, the genes producing CIT enzymes were more prevalent mainly in contrary to the study conducted by Jean et al,2017 where most of the E.coli (11.7%) harbored CMY-2 producing enzyme (18).…”
Section: Resultscontrasting
confidence: 89%
“…Our study revealed a prevalence of the AmpC producing gene of 14.75% among ESBL producing Enterobacteriaceae. In our study, we found out that among all the AmpC producers, the genes producing CIT enzymes were more prevalent mainly in contrary to the study conducted by Jean et al,2017 where most of the E.coli (11.7%) harbored CMY-2 producing enzyme (18).…”
Section: Resultscontrasting
confidence: 89%
“…Our data reveal that shifting the prevalence of AmpC genes occurred during the short time in our country. In addition, according to Jean et al's [22] study, the most abundant AmpC beta-lactamase variant among clinical isolates of K. pneumoniae in Asia-Pacific region was DHAM.…”
Section: Discussionmentioning
confidence: 99%
“…Since the incidence of infections due to ESBL + E and AmpC-positive Enterobacteriaceae in Thailand has continuously increased [14] , this study was carried out to gain a better understanding of the intestinal carriage of ESBL + E and identify risk factors for ESBL + E carriage in a community setting in Northern Thailand. Furthermore, this study was extended to include the carriage rate of AmpC-positive Enterobacteriaceae.…”
Section: Introductionmentioning
confidence: 99%